Fostering life hope in urban green spaces through brief online mindfulness: findings from four studies with park visitors - Luo, Mengke; Zhang, Weiyi (Frontiers in Psychology, 2025)
Contrary to the prevailing view that technology detracts from nature, this research demonstrates that digitally-guided mindfulness can act as a powerful amplifier of the psychological benefits of Urban Green Spaces (UGS). Across four interconnected experiments, we reveal how and for whom this synergy works to enhance life hope. Building on Attention Restoration, Broaden-and-Build, and Hope theories, our investigation shows that an online mindfulness intervention in a park setting significantly boosts life hope more than a self-guided offline practice (Experiment 1). This effect is mediated by the induction of flow, a state of deep absorption in the present moment (Experiment 2). Furthermore, our model reveals crucial boundary conditions: this positive, flow-driven pathway is significantly stronger for individuals experiencing higher levels of spirituality (Experiment 3) and possessing a greater sense of meaning in life (Experiment 4). Collectively, these findings offer a novel, evidence-based framework showing that personalized, digitally-delivered interventions can transform UGS into more effective therapeutic landscapes. This provides actionable insights for urban planners and digital health developers to create scalable, accessible, and highly effective nature-based solutions for promoting public mental wellbeing. Future research should address limitations by incorporating objective measures and examining long-term effects.